1999
DOI: 10.1096/fasebj.13.14.2051
|View full text |Cite
|
Sign up to set email alerts
|

Markers of capacity to utilize fatty acids in human skeletal muscle: relation to insulin resistance and obesity and effects of weight loss

Abstract: A number of biochemical defects have been identified in glucose metabolism within skeletal muscle in obesity, and positive effects of weight loss on insulin resistance are also well established. Less is known about the capacity of skeletal muscle for the metabolism of fatty acids in obesity-related insulin resistance and of the effects of weight loss, though it is evident that muscle contains increased triglyceride. The current study was therefore undertaken to profile markers of human skeletal muscle for fatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

28
350
1
7

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 437 publications
(394 citation statements)
references
References 57 publications
28
350
1
7
Order By: Relevance
“…This is in agreement with previously reported findings [18,36] after moderate weight loss, demonstrating that even massive weight reduction is without effect on CPT1 expression. In contrast to physical exercise-mediated PGC1A upregulation, PGC1A upregulation due to weight reduction was not associated with an increase of CPT1 expression.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…This is in agreement with previously reported findings [18,36] after moderate weight loss, demonstrating that even massive weight reduction is without effect on CPT1 expression. In contrast to physical exercise-mediated PGC1A upregulation, PGC1A upregulation due to weight reduction was not associated with an increase of CPT1 expression.…”
Section: Discussionsupporting
confidence: 94%
“…Their downregulation, after weight reduction, has been proposed as a possible reason for limited weight loss and/or relapse to obesity [18,23]. Skeletal muscle is a major contributor to overall energy expenditure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the role of mitochondria in the pathogenesis of insulin resistance and diabetes is still unclear. In vastus lateralis muscles from obese insulin-resistant patients after weight loss, no increase in oxidative enzyme activities was reported, in spite of an improvement of insulin sensitivity [42]. In addition, Toledo and collaborators [37] have reported that weight loss, without physical exercise, in obese patients ameliorates insulin sensitivity with no effects on muscle mitochondrial capacity.…”
Section: Discussionmentioning
confidence: 99%